2019
DOI: 10.1002/ajoc.201900113
|View full text |Cite
|
Sign up to set email alerts
|

A Redox Auxiliary Strategy for Pyrrolidine Synthesis via Photocatalytic [3+2] Cycloaddition

Abstract: Cycloaddition reactions can be used to efficiently assemble pyrrolidine rings that are significant in a variety of chemical and biological applications. We have developed a method for the formal cycloaddition of cyclopropyl ketones with hydrazones that utilizes photoredox catalysis to enable the synthesis of a range of structurally diverse pyrrolidine rings. The key insight enabling the scope of photoredox [3 + 2] cycloadditions to be expanded to C=N electrophiles was the use of a redox auxiliary strategy that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Taking the above experiments and observations, we present our working mechanistic understanding (Scheme ). After that absorption of a photon, an initial singlet photocatalyst rapidly undergoes intersystem crossing to yield the triplet excited-state photocatalyst. , Based on redox potentials, the reaction is expected to proceed through a reductive quenching cycle in which the triplet photocatalyst ( E 0 (Ir II /Ir III *) = −1.04 V) is reduced by an amine ( E ox ca. 0.5 V vs SCE).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking the above experiments and observations, we present our working mechanistic understanding (Scheme ). After that absorption of a photon, an initial singlet photocatalyst rapidly undergoes intersystem crossing to yield the triplet excited-state photocatalyst. , Based on redox potentials, the reaction is expected to proceed through a reductive quenching cycle in which the triplet photocatalyst ( E 0 (Ir II /Ir III *) = −1.04 V) is reduced by an amine ( E ox ca. 0.5 V vs SCE).…”
Section: Resultsmentioning
confidence: 99%
“…Searching for optimal reaction conditions revealed that the mass balance for the products of the reaction, apart from several major products, consisted of a complex mixture of oligomers. Upon screening the photocatalysts (Table , entries 1–9), it was discovered that bis-4-( tert -butyl)-2-(4-( tert -butyl)­phenyl)­pyridine-4,4′-di- tert -butyl-2,2′-bipyridyl iridium­(III) hexafluorophosphate (Ir­(dtbbpy)­(dtbppy)­2PF 6 ) ( PC3 ), a somewhat oxidizing , and sterically bulky photocatalyst that has thus far been relatively underrepresented in the literature, was optimal, having a triplet-state emissive energy of 49.4 kcal/mol and energies of E 0 (Ir II /Ir III *) = −1.04 V and E 0 (Ir II /Ir III )= +1.13 V. While PC5 had a similar outcome in terms of the intended product, the reaction produced many minor side products and was therefore rejected to the simplify purification.…”
Section: Resultsmentioning
confidence: 99%
“…This has also been exploited by Yoon et al in studies of [3+2] cycloaddition reactions of redox-active cyclopropyl ketones (Scheme 45). 91 In the presence of Ir(4-CF 3 -ppy) 3…”
Section: Review Synthesismentioning
confidence: 99%
“…This has also been exploited by Yoon et al in studies of [3+2] cycloaddition reactions of redox-active cyclopropyl ketones (Scheme 45). 91 In the presence of Ir(4-CF 3 -ppy) 3 and stoichiometric Yb(OTf) 3 , cyclopropane 4.29 underwent ring opening and radical addition to hydrazones such as 4.30 to afford N-aminopyrrolidines 4.31. The presumed mechanism involves oxidative quenching of the photocatalyst by the cyclopropyl ketone 4.29 to afford a ketyl radical 4.34, followed by cyclopropylcarbinyl radical rearrangement to distonic anion radical 4.35.…”
Section: Review Synthesismentioning
confidence: 99%
“…Multifluorinated (partially fluorinated) arenes exhibit markedly altered properties compared to the parent nonfluorinated molecules and have potential applications in materials, pharmaceuticals, and other fields . The fluorinated arenes are not naturally occurring, and efficient methods for synthesis of multifluorinated arenes remain underdeveloped .…”
mentioning
confidence: 99%